Theoretical study on core-mode to radiation-mode coupling in chiral fiber long-period gratings. (1st July 2017) - Ren, Kaili; Ren, Liyong; Wang, Yingli; Lin, Xiao; Liang, Jian; Xu, Yiping; Ju, Haijuan
Abstract: The chiral fiber long-period gratings (CLPGs) could be fabricated by twisting a high-birefringence (Hi-Bi) fiber. However, when it is immersed into a material whose refractive index (RI) is higher than that of the cladding, there exists a complicated coupling between the core modes and the radiation ones. In this paper, for the first time to our knowledge, we theoretically investigate the mode coupling characteristics in such a CLPG. It is found that, owing to a strong mode transfer from the co-handed core mode to continuous radiation ones under the phase-matching condition, the CLPG can be regarded as a broadband circular polarizer since only the cross-handed circularly polarized light is left when a linearly polarized light is injected. Furthermore, the influence of the RI of the surrounding medium on the bandwidth and extinction ratio of this circular polarizer is investigated in detail. As a result, a broadband all-fiber circular polarizer can be constructed. Considering its simple configuration, it might have some potential applications, such as filters, broadband polarizers, and sensors. Highlights: For CLPG, a radiation coupled-mode model is established. A novel broadband all-fiber circular polarizer can be constructed. For the radiation mode coupling, the effect of RI on CLPG is explored. Comparing with traditional CLPG, our CLPG could operate with a broader bandwidth.